It's all about the individual's right to choose: A qualitative study of Australian culturally and linguistically diverse nurses' knowledge of and attitudes to voluntary assisted dying. Issue 1 (February 2022) - Penman, Joy; Malik, Gulzar; Rogerson, Kelly; Murphy, Julie; Zhong, Yaping; Johnson, Claire E
Abstract: Background: Nurses have a fundamental role in providing care for people at the end of life. Some nurses from culturally and linguistically diverse (CALD) backgrounds may have diverse opinions about death which may affect their views about voluntary assisted dying (VAD) and may impact on the care they provide. To date, there has not been a focus on the views of nurses from different CALD backgrounds on VAD. The implementation of VAD may place them at risk of ethical, moral, social and professional distress. Aims: The study was conducted to determine the knowledge and attitudes of Victorian nurses from CALD backgrounds about VAD. The other aims were to understand their perceptions about how VAD might affect their professional practice and recommend strategies that might assist in their readiness and preparation for exposure to VAD. Methods: This study used a qualitative descriptive approach. The knowledge and attitudes toward VAD of nurses from CALD backgrounds were explored using face-to-face focus group discussion and in-depth interviews. Interviews were transcribed verbatim and thematic analysis was undertaken. Findings: Seventeen female and four male nurses from CALD backgrounds were recruited through partner healthcare organisations. They came from nine different countries, with ages ranging from late 20s to 60 years. All had experienced caring for individuals at the end stage of life, and about half had experienced being asked directly about VAD. Three themes emerged from the focus group meeting and interviews. These were: 'Mixed level of knowledge about VAD', 'Conflicting cultural and religious beliefs' and 'Supremacy of professional and ethical values and attitudes'. Discussion: All of the participants were aware of VAD, but the depth of knowledge varied. Some attitudes revealed that their cultural and religious beliefs and practices conflicted with their views and practices related to VAD, but they considered the interest, autonomy, and decisions of the people they served as the primary focus. Most nurses were able to set aside and distinguish their current and past beliefs, backgrounds, culture and ethnicity, and prioritised their patients' wellbeing and choices. For these nurses, professional and ethical values and attitudes were significant determinants of their personal belief systems when it came to VAD. This study provided a greater understanding of CALD nurses' awareness, knowledge and attitudes about VAD, the impact of culture, religion and other variables on their perceptions of assisted dying and on professional practice, as well as the identification of strategies to increase the capacities of nurses in managing assisted dying. Conclusion: The findings of this study indicate a need for a broad-based educational program in VAD focused on building the capability of nurses who may lack knowledge about VAD and strategies to deal with VAD, and/or are experiencing difficulty reconciling their own cultural and/or religious beliefs with patients' decisions to opt for voluntary assisted dying.